Legal Protection of Medical Staff in Hospitals during The Covid-19 Pandemic Era - Elli Ruslina; Rita Sekarsari (International Journal of Latin Notary, 2020)
This research begins with the Covid-19 pandemic which requires serious control because it has had a dangerous impact on society, especially health workers in hospitals. The research focus is aimed at the legal protection of health workers in hospitals and the state's responsibility for health workers. The research method used is library research, which is a method used by studying literature such as books, legislation and articles, journals related to the subject matter. Primary data used in field research, through interviews with related parties, namely hospitals and health workers. The focus of the discussion is to emphasize more on laws and regulations related to Social Distancing / Physical Distancing policies as regulations for legal protection of health workers as the frontline and state responsibility for health workers. The results showed that various laws and regulations as a policy for handling Covid-19 cannot be realized concretely in the field because they are related to different bureaucracy and implementation. The role of the state in the responsibility for health workers is not The responsibility of the state in this case is that the Government and Administrators of Health Service Facilities are obliged to ensure the sustainability of the availability of standardized Personal Protective Equipment (PPE) for health workers who work in health service facilities.